The speeches of Antony and Crassus in the De oratore: forensic usus, Philo of Larissa and Antiochus of Ascalon - Reggi, Giancarlo (Ciceroniana On Line, 2021)
In the De oratore, Cicero’s portrait of Antonius is deeply influenced both by Cato and Academic philosophy; L. Crassus, on the other hand, is characterised by the range of his philosophical interests. The reversal of the Gorgias-Callicles relationship with reference to the Socrates-Plato relationship, the βίος σύνθετος ideal that finds its culmination in political life, the paradigm of ἐγκύκλιος παιδεία that includes philosophy – all are derived from the teachings of Antiochus of Ascalon. Cicero’s original contribution may be the synthesis of philosophy and rhetoric and the attack on the fragmentation of knowledge. Philo of Larissa exerts a clear influence on both Crassus and Cicero’s position on ὑπόθεσις-causa and θέσις-quaestio. Conceptualising rhetoric as a στοχαστικὴ τέχνη, as well as the terminology and practice of disputatio in utramque partem, are likely theoretical coordinates shared by both Philo and Antiochus.